Dual‐Stimuli Responsive Nanotheranostics for Multimodal Imaging Guided Trimodal Synergistic Therapy. Issue 6 (15th November 2016) - Fang, Shan; Lin, Jing; Li, Chunxiao; Huang, Peng; Hou, Wenxiu; Zhang, Chunlei; Liu, Jingjing; Huang, Sisi; Luo, Yongxiang; Fan, Wenpei; Cui, Daxiang; Xu, Yunsheng; et al.
Abstract : Multimodal imaging guided synergistic therapy promises more accurate diagnosis than any single imaging modality, and higher therapeutic efficiency than any single one or their simple "mechanical" combination. Herein, we report a dual‐stimuli responsive nanotheranostic based on a hierarchical nanoplatform, composed of mesoporous silica‐coated gold nanorods (GNR@SiO2), Indocyanine Green (ICG), and 5‐fluorouracil (5‐FU), for in vivo multimodal imaging guided synergistic therapy. The 5‐FU loaded ICG‐conjugated silica‐coated gold nanorods (GNR@SiO2‐5‐FU‐ICG) was able to response specifically to the two stimuli of pH change and near‐infrared (NIR) light irradiation. Both the NIR light irradiation and acidic environment accelerated the 5‐FU release. Meanwhile, the heat generation and singlet oxygen production can be induced by GNR@SiO2‐5‐FU‐ICG upon light irradiation. Most intriguingly, the nanoplatform also promises multimodal imaging such as two‐photon luminescence, fluorescence, photoacoustic, photothermal imaging, as well as trimodal synergistic therapy such as photothermal therapy (PTT), photodynamic therapy (PDT), and chemotherapy. The cancer theranostic capability of GNR@SiO2‐5‐FU‐ICG was evaluated both in vitro and in vivo. The trimodal synergistic therapy with the guidance of multimodal imaging exhibited remarkably enhanced treatment efficacy. This concept of a hierarchical nanoplatform integrates multiple diagnostic/therapeutic modalities into one platform, which can potentially be applied as personalized nanomedicine with drug delivery, diagnosis, and treatment. Abstract : A dual‐stimuli responsive nanotheranostic based on 5‐fluorouracil loaded indocyanine green‐conjugated silica‐coated gold nanorods is developed for multimodal imaging such as two‐photon luminescence, fluorescence, photoacoustic, photothermal imaging, as well as trimodal synergistic therapy such as photothermal therapy, photodynamic therapy, and chemotherapy.